Development of a novel MR clutch featuring tooth-shaped disc - Nguyen, Quoc Hung; Diep, Bao Tri; Nguyen, Duy Hung; Nguyen, Van Bien; Vu, Van Bo; Do, Qui Duyen (Vietnam Journal of Mechanics, 2021)
In this research, we focus on development of a new configuration of magneto-rheological fluid (MRF) based clutch (MRC) featuring a tooth-shaped disc with multiple teeth acting as multiple magnetic poles of the clutch. The tooth-shaped disc is placed in a clutch housing composed of the left housing and the right housing. The inner face the housing also has tooth shaped features mating with the teeth of the disc through the working MRF. Excitation coils are placed directly on stationary winding cores placed on both side of the clutch housing. An air gap of 0.3 mm is left between the housing and the winding cores to ensure the housing can freely rotate against the winding cores. After the introductory part, configuration of the MRC is introduced and the transmitted torque of the MRC is derived. An optimization process to minimize the overall volume of the proposed clutch, which can generate a required maximum braking torque, is then conducted. The optimal results show that the overall volume of the proposed MRC is significantly reduced compared to a referenced conventional MRC (0.159 m3 vs. 0.295 m3). A prototype of the proposed MRC is fabricated for experimental works and good agreement between the experimental results and simulated ones is archived.